Analysis of the Effect of Liquidity, Profitability and Debt Policy on Firm Value with Dividend Policy as Moderating Variable: Analisis Pengaruh Likuiditas, Profitabilitas dan Kebijakan Hutang Terhadap Nilai Perusahaan dengan Kebijakan Dividen sebagai Variabel Moderasi - Wanti, Fadilah Herdiana; Sari, Herlinda Maya Kumala (Indonesian Journal of Law and Economics Review, 2022)
The purpose of this study is to analyze the effect of liquidity, profitability, and debt policy on firm value with dividend policy as a moderating variable on LQ45 index companies listed on the Indonesia Stock Exchange for the 2018-2020 period. This study is a quantitative study using purposive sampling technique with a sample of 14 companies from a population of 62 companies and tested by multiple linear regression analysis and MRA (Moderated Regression Analysis) using SPSS version 22 software. The results showed that liquidity (CR) had a significant negative effect. on firm value (PBV), profitability (ROA) has a significant positive effect on firm value (PBV), debt policy (DER) has no effect on firm value (PBV), dividend policy (DPR) is able to moderate by significantly weakening the effect of liquidity (CR ) on firm value (PBV), dividend policy (DPR) is able to moderate by significantly strengthening the effect of profitability (ROA) on firm value (PBV) and dividend policy (DPR) is not able to significantly moderate the effect of debt policy (DER) on firm value. (PBV).